THE THE IMPORTANCE OF LEGAL INSTRUMENTS FOR THE PREVENTION OF WORK INJURIES AND OCCUPATIONAL DISEASES - Nikolić, Milica (Glasnik Advokatske komore Vojvodine, 2023)
The author deals with the issue of work injuries and occupational diseases. Through the analysis of both domestic legislation and comparative law, the author tried to point out the importance of legal instruments for the suppression and prevention of work injuries and occupational diseases. Taking into consideration that there is a big gap between the normative framework of the Republic of Serbia and practice, the author puts forward the thesis that some existing legal provisions encourage evasion of reporting work injuries and occupational diseases. The author conducted an empirical research using survey and in-depth interview, all with the aim of obtaining data on the frequency of injuries at work, as well as whether they are reported, and if not, what is the cause. The survey was anonymous and based on the principle of free sample. The interview was conducted with several people working in a woodworking company. The results of the survey show that almost half of the participants have suffered personally or know someone who has suffered a work injury or an occupational disease. Of the participants who personally suffered an injury at work, one large percentage stated that the employer didn’t report it. Over half of all participants know the domestic legal provisions on salary compensation and a large number of participants see in those provisions possible reason for evasion of reporting work injuries and occupational diseases. When it comes to the interview, the respondents-employees had fear when giving answers, they answered the questions very briefly and checked several times whether it was really all anonymous. However, the results of the interview also showed that employees understand that employers have no economic interest in reporting injuries at work. On the basis of the conducted research, the conclusion is that reporting work injuries and occupational diseases are of great importance and, as such, must be paid more attention. It seems that it is necessary to change the existing inadequate legal provisions in the form of "direct responsibility of the employer for the costs for work injuries“, also it seems a good solution to set up a special insurance fund for work injuries and occupational diseases. Keywords: work injury; occupational diseases; safety and health at work; prevention; reporting work injury.